The Effect of Sustainability Reports on Company Value (Empirical Study of Infrastructure Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period) - Fitriya Muslimah Zam-Zam; Hendrik Gamaliel; Sherly Pinatik (PT FORMOSA CENDEKIA GLOBAL, 2023)
Investors are interested in investing their shares by looking at the company's value which is reflected in the stock price. In addition to financial information, information about company operations is needed, namely the sustainability report. This study aims to determine the effect of sustainability reports on firm value through differences in firm value between companies that publish sustainability reports and companies that do not publish sustainability reports. This type of research is quantitative research using descriptive analysis methods and independent different tests. The population in this study are infrastructure sector companies listed on the IDX (2017-2021). The sampling technique used purposive sampling of 40 companies. The results of the study show a significant effect on firm value between companies that publish and do not publish sustainability reports, there is a difference between large companies and small companies that publish sustainability reports, there is no difference between large companies that publish and do not publish sustainability reports.